The Architecture of the Church of St Patrick and St Brigid - Tierney, Andrew (My University, 2021)
The post-famine period saw a boom in Catholic church building across Ireland. County Kildare, as home to Maynooth College (1795; 1845) and Clongowes Wood College (1814), was at the forefront of Catholic religious revival in 19th century Ireland. SS Patrick and Brigid (1876-1884) was one of several churches in the county built by rural congregations in the new Gothic Revival style, such as Donaghstown (1860-63), Allen (1868), Prosperous (1869). As early as the 1860s there had been an idea of building a new chapel in the village, as parishioner Thomas M. Donellan had included in his will of 1866 ‘£200 in trust for the purpose of assisting to build a new chapel at Clane’. The original Catholic chapel in Clane of 1805 was of a vernacular type, internally T-shaped in plan, that had been built across Ireland after the relaxing of the penal laws in the late eighteenth century. The construction of the new church, directly behind the site of the old, took place under the stewardship of the Rev. Patrick Turner, an energetic priest of the parish and a champion of tenant rights. His Latin-inscribed white marble monument, inside the church, records his death just five years after its completion.
PUBLISHED
Keywords: Creative Arts Practice; Identities in Transformation; Making Ireland; 19th-Century Architectural History; Art and Religion; Irish History; Irish architectural history